Planning the sustainable development of historic neighbourhoods through the management of significance - Matthew Nouch (Cidades, Comunidades e Território)
In Santarém, as in several Portuguese historic urban centres, population decline and aging have compromised social cohesion and economic vitality, and parts of the Historic Centre have visibly deteriorated, resulting in risks to the public of crumbling façades. Sustainable development in urban areas must involve a reorientation of spatial planning policies to integrate older areas into wider urban and regional development frameworks, considering them as part of the wider territory. This paper proposes that the operationalisation of the recommendations of the Historic Urban Landscape (HUL) approach can provide robust evidence, co-produced with local communities, supporting sustainable urban planning policies, and that such an approach is wholly consistent with EU and national planning and conservation legislation. Through focusing on the values, meanings and significance of place, the processes shaping the HUL of an empirical test neighbourhood, the Mouraria in Santarém, are brought into focus.